A Source Code Plagiarism Detecting Method Using Sequence Alignment with Abstract Syntax Tree Elements - Kikuchi, Hiroshi; Goto, Takaaki; Wakatsuki, Mitsuo; Nishino, Tetsuro (International journal of software innovation, 2015)
Learning to program is an important subject in computer science courses. During programming exercises, plagiarism by copying and pasting can lead to problems for fair evaluation. Some methods of plagiarism detection are currently available, such as sim. However, because sim is easily influenced by changing the identifier or program statement order, it fails to do enough to support plagiarism detection. In this paper, the authors propose a plagiarism detection method which is not influenced by changing the identifier or program statement order. The authors also explain our method's capabilities by comparing it to the sim plagiarism detector. Furthermore, the authors reveal how our method successfully detects the presence of plagiarism.